Management Program Implementation of Performance Monitoring and Control Systems Benefits as Quality Control and Teacher Competence in Banyuwangi District - Istu Handono; Rudy Handoko; Endang Indartuti; Ute Chairuz M. Nasution (LPPM of NAROTAMA UNIVERSITY, 2023)
Teachers who get certification are entitled to a professional allowance. The government hopes that with this allowance, teachers can improve their welfare and performance. But unexpectedly, after receiving the professional allowance, teachers are not compensated with good quality and competence. Related to this, the Banyuwangi Regency government made improvements through the Education Office Branch. A Management System for Monitoring and Control of Performance and Allowances (SRITANJUNG) management program was launched to control teacher quality and competency. This study aims to build an implementation model for the Sritanjung Program as a quality control and appropriate teacher competency. Factors that support or inhibit will be sought and try to find a solution. This study uses a descriptive qualitative method by collecting data in the field through interviews and questionnaires to all parties involved. The results showed that 1) the implementation of the program as a quality control and teacher competence in the process there are problems with legality, attitude and character of supervisors and principals, target targets/teachers, and tools. While the supporting factors for program implementation as control are: (a) the existence of implementer intentions and agreements, (b) the existence of a legal umbrella, (c) application support, and (d) the availability of implementor resources that are ready. While the inhibiting factors are (a) policy; assignment legality for school supervisors and principals, (b) tools; teacher's computer equipment, frequent errors, incomplete features, and internet signal, (c) systems and processes; lack of clear information about the program, and (d) from human resources; not all teachers are familiar with applications, honesty of information from teachers, weak mastery of information technology and computers, allocation of allowances and busyness of teachers. Meanwhile, the program implementation model for quality control and teacher competence that has been built and is appropriate is the Co-Han Model, which is presumably the initial solution. The Co-Han model is a combination of the old program implementation model and some elements of the COCO control model. This new model involves elements of attitude and characteristics of implementers and targets. Involving the elements of attitude and character in the form of goals, commitment, and abilities is considered very important. With a good attitude and character, it is hoped that the program can be implemented properly too, so that the goals will be easily achieved. The combination of management as a system, as well as commitment and ability as a character will greatly influence program objectives. This is considered a very effective, necessary and new combination in a program implementation as control.